Design of a Translation Project to Develop the Thematic Translation Competence - Morales-Santibanez, A (UNIV PERUANA CIENCIAS APLICADAS, 2017)
This article describes the first step in a Teaching Innovation Project in Universidad de Santiago de Chile, which includes the project s design and the methodological aspects required for its implementation and evaluation. Experts from different academic units will give students real translation assignments (specified in a translation brief) and will support them in the process so as to contribute to the development of their thematic translation competence. This project will be implemented in the Specialized Social Science English-Spanish Translation course (4th year) of the Bachelor of Linguistics Applied to Translation degree program during the September 2017 semester. The proposal is based on contributions from Kiraly (2000) stating that the most effective way for students to develop professional competences is by offering them opportunities to interact with their classmates and with experts. Within this project, various methodological guidelines and assessment instruments-with different purposes, applied at different times, and from distinctive agents-were designed so as to meet the need to obtain a global picture of the entire process. The implementation of this didactic strategy will contribute to the systematization of a teaching practice which, although being used in translators training in Universidad de Santiago, lacks a formal design and specific assessment instruments that would allow replicating it in other specialized translation courses at a local and national level.